ANALISA PERSEPSI HARGA TERHADAP MINAT BELI ULANG MELALUI PERCEIVED VALUE PADA HOTEL X SURABAYA - Andrew Pratama; Joseph Ardhy (Jurnal Hospitality dan Manajemen Jasa, 2017)
This study was conducted to analyze the influence of perceived price on repurchase intention through perceived value. This research was conducted at Hotel X Surabaya by spreading questionnaires to guests who had stayed at Hotel X Surabaya. The data was collected and selected from 100 spreaded questionnaires. From those, questionnaires that could be processed was 87 questionnaires which then analyzed by applying structural equation modeling (SEM) and processed with SmartPLS. The result of research shows that perceived price has positive and significant effect to perceived value. Perceived price and perceived value affects repurchase intention positively and significantly. The results of this study also prove the role of perceived value as an intervening variable in mediating the influence of price perceptions on repurchase interest..